Synchronization in pth Moment for Stochastic Chaotic Neural Networks with Finite-Time Control. (3rd January 2019) - Xu, Yuhua; Wang, Jinmeng; Zhou, Wuneng; Wang, Xin
Abstract : Finite-time synchronization in pth moment is considered for time varying stochastic chaotic neural networks. Compared with some existing results about finite-time mean square stability of stochastic neural network, we obtain some useful criteria of finite-time synchronization in pth moment for chaotic neural networks based on finite-time nonlinear feedback control and finite-time adaptive feedback control, which are efficient and easy to implement in practical applications. Finally, a numerical example is given to illustrate the validity of the derived synchronization conditions.